A MODERN VIEW ON THE PROBLEM OF NON-DEVELOPING PREGNANCY - Akhmedov , F.K.; Akhmadzhonova, G.M.; Akhmadalieva, N.Zh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background. The problem of miscarriage, especially in the early stages, is of great importance both from a medical and social point of view. Approximately 80% of cases of spontaneous miscarriages occur in the first trimester. Among the various types of miscarriage, non-developing pregnancy attracts special attention, the multifactorial nature of which is beyond doubt. Aim. to study the expression of interleukin-2 (IL-2) in pregnant women with fetal growth retardation and spontaneous abortion. Materials and methods. We studied the pregnant women involved in the study, dividing them into 3 groups: Group 1 - complicated by fetal failure (n=50); II group - complicated by spontaneous miscarriage (n=54). control group - group of pregnant women with physiological pregnancy (n=30). Results. The results of our studies showed that the concentration of interleukin-2 (IL-2) in the blood of pregnant women with complications of fetal malformations in group I was 51.4±0.32 pg/ml, and in women included in group II, its level was 41.2±0.30 pg/ml. In pregnant women in the control group, this indicator was 18.2±0.22 pg/ml (P<0.001). ROC curve for the indicator “Interleukin-2 (IL-2) pg/ml”. The area under the curve was 0.92±0.12 (95% CI (confidence interval) 0.645.... 0.920), p=0.08, indicating that IL-2 can be used as a predictor of fetal growth retardation. In our study, the plasma IL-2 level in women with fetal growth retardation was 51.4±0.32 pg/ml (specificity 64%, sensitivity 92%). Conclusions. Thus, our study found a positive correlation between interleukin-2 (IL-2) and fetal growth retardation. It also showed that IL-2 is a reliable marker for fetal growth retardation alone.